Farmers and scientists in AR4D: Looking at a watershed management project through an STS lens - Habermann, Birgit; Vogl, C.R.; Mekonnen, Kindu; Bekele, K.; Felt, U. (Informa UK Limited, 2021)
Agricultural Research for Development (AR4D) provides the interface for the meeting of farmers and scientists. This is a meeting of different social worlds, contesting agendas, cultures of cooperation and networks of actors. Like in other disciplines, scientists in AR4D have developed their own culture of science. However, the role of their culture of science in the negotiations and encounters with farmers' social worlds is rarely discussed. Analysing AR4D with a theoretical framework based on Science and Technology Studies (STS) helps us to highlight important issues of power and access in AR4D. The goal of this paper is to demonstrate how the introduction of certain technologies has interacted with the lives of people in an AR4D project in Ethiopia, and to highlight the potential and limitations of applying STS to AR4D. We interviewed farmers, scientists, extensionists, policy makers and donors associated with an AR4D project in the Ethiopian Highlands using qualitative social research approaches. Akrich's theory on scripts provided the theoretical framework for analysis. Our findings provide examples for the re-inscription of technology and access in an AR4D project, leading to trade-offs and shifting of power between different actors. We conclude that understanding AR4D as part of a network of actors with its own culture of science provides an essential learning ground. We recommend STS to be applied more widely in AR4D to explore the nature of these networks to highlight what makes technology work for users in the long term.